Glandular hyperplasia of endometrium in women with hormonal replacement therapy - Harasim, Marek; Borowski, Dariusz (Menopause Review/Przegląd Menopauzalny, 2011)
Objectives: Abnormal uterine bleeding is one of the most common problems in the perimenopausal period. The most common cause of perimenopausal bleeding is endometrial hyperplasia (EH) The diagnosis of endometrial hyperplasia in Poland is still established by D&C (dilatation and curettage) and endometrial biopsy. There are many controversies about the association between hormonal replacement therapy and development of endometrial hyperplasia. The aim of this study was to evaluate the rate of EH in HRT taking patient population and to assess the correlation between endometrial hyperplasia and the type of HRT. Material and methods : The study was performed at the Department of Histopathology of a non-public health care establishment in Sosnowiec. The study group was divided into two groups. The first consisted of 151 women with abnormal uterine bleeding who took HRT (77 patients took cyclic HRT and 74 – continuous combined HRT). The second group consisted of 1754 women with abnormal uterine bleeding without HRT. The study group consisted of 1905 tissue samples (D&C and endometrial biopsy) taken from patients between 45 and 60 years old with abnormal uterine bleeding. Result and conclusions : There is no case of EH in a group with cyclic HRT. There are 9 cases (12.2%) of simple EH in a group with continuous combined HRT. There is no case of complex EH in both HRT groups. There is no statistical significance in occurrence of endometrial hyperplasia between women taking HRT for less or more than one year. 1. Occurrence of endometrial hyperplasia is significantly lower in the HRT group in comparison with the group without HRT. 2. Cyclic HRT is a preventing factor in development of endometrial hyperplasia.